Synthesis of Tri-Substituted Olefin Derivatives from 1-Alkene-1, 2-Diboronic Esters via Sequential Suzuki-Suzuki Coupling Reaction and Their Biological Activity. (21st October 2022) - Kerketta, Manoranjan; Mali, Maruti; Sridhar, Gattu; Sharma, Gangavaram V. M.; Vankudoth, Jayaram
Abstract: Substituted Olefin-based compounds are attractive targets in the design of novel chemical structures for the discovery of new drugs. In the current study, we have synthesized a series of new tri-substituted olefin derivatives (4a–4p) and their chemical structures were confirmed by spectroscopic techniques. The series of molecules were evaluated for anti-cancer potential against four human cancer cell lines such as MDA-MB-232, HepG2, MCF-7 and HEK293. Among the evaluated compounds, ten compounds 4a, 4c, 4d, 4f, 4g, 4h, 4k, 4l, 4m and 4p displayed more potent anticancer activity. Along with anti-cancer we evaluated antimalarial activity of all compounds toward plasmodial strain PF3D7 via SYBR Green I assay approach and screened their Anti tuberculosis interest toward Mycobacterium tuberculosis. Graphical Abstract: UF0001